"A Parliament of Man Become a Parliament of Women": Performing Femininity and the State Through Mediated Civic Ritual in Ontario, 1900–1940. Issue 1 (11th December 2012) - Cairns, James
Abstract This article analyses representations of bourgeois femininity in early twentieth century newspaper coverage of the ceremonial Opening of the Legislature in Ontario, Canada's largest and most populous province. Building on theories that shed light upon the complex processes of material and symbolic reproduction required to reproduce "the idea of the reality of the state, " I argue that mass mediated representations of women's bodies and fashions during this key civic ritual contributed to state formation. The article demonstrates the ways in which newspaper coverage of a particular type of gendered performance reflected and reinforced an imperialist and patriarchal provincial state‐building project.